IMPLEMENTACIÓN DE UN SISTEMA CONTABLE A LA JUNTA ADMINISTRADORA DE AGUA POTABLE Y ALCANTARILLADO SANITARIO DE LA PARROQUIA SAN PEDRO DE LA BENDITA PERIODO ENERO-ABRIL 2014 - SURIAGA OCHOA, KAREN ANDREA (2016)
This research paper titled "Deploying an accounting system management board WATER AND SANITARY SEWER PARISH SAN PEDRO OF THE HOLY January-April 2014", was developed as established in the Regulation of Academic System National University of Loja, in compliance with a pre-qualify the degree of Engineer in Accounting and Auditing, Auditor CPA requirement. With the implementation of Accounting System were met the objectives set, which came to strengthen the financial management of the Board, becoming an important contribution to the growth and development of their economic activities, starting with the design of the Plan and User accounts according to the needs thereof; He continued with the preparation of the initial inventory, recording the value of assets and liabilities with which opening is given the fiscal year, then verifying the source documentation for the preparation of the memorandum of operations and proceed to Journalize in Daybook orderly as systematically; then he continued with the majorization of each of the accounts from the exercise to continue the Trial Balance, Worksheet, finally the presentation of financial statements, in which the accuracy of economic activities is captured and the result operations of the Board, by which he could define, clearly present each of the accounts and their balances, revealing the economic benefits obtained within the given for the study period. Finally the application of financial 5 indicators expressed in quantitative and qualitative terms the situation of the entity. It is concluding that the accounting system provided orderly and systematic information from the initial inventory to the financial statements, so that the Board must consider the current research work and continue with it so you can get relevant and reliable financial statements for sound decision making.